2014
DOI: 10.1093/molehr/gau043
|View full text |Cite
|
Sign up to set email alerts
|

Gene copy number alterations in the azoospermia-associated AZFc region and their effect on spermatogenic impairment

Abstract: abstract:The azoospermia factor c (AZFc) region in the long arm of human Y chromosome is characterized by massive palindromes. It harbors eight multi-copy gene families that are expressed exclusively or predominantly in testis. To assess systematically the role of the AZFc region and these eight gene families in spermatogenesis, we conducted a comprehensive molecular analysis (including Y chromosome haplogrouping, AZFc deletion typing and gene copy quantification) in 654 idiopathic infertile men and 781 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
(51 reference statements)
0
34
2
2
Order By: Relevance
“…The epidemiological evidence is corroborated by molecular genetic data indicating a higher prevalence of genomic instability (microdeletions and/or duplications) in specific “hot‐spots” of the AZF sex‐coding region of Y chromosome, which is a genetic marker of impaired spermatogenesis (Lu et al ), can be transmitted to the offspring (Jungwirth et al ) and may predispose to severe congenital abnormality when spermatozoa are formed (Diemer and Desjardins ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The epidemiological evidence is corroborated by molecular genetic data indicating a higher prevalence of genomic instability (microdeletions and/or duplications) in specific “hot‐spots” of the AZF sex‐coding region of Y chromosome, which is a genetic marker of impaired spermatogenesis (Lu et al ), can be transmitted to the offspring (Jungwirth et al ) and may predispose to severe congenital abnormality when spermatozoa are formed (Diemer and Desjardins ).…”
Section: Discussionmentioning
confidence: 92%
“…The AZFc region contains eight multicopy gene families, which are believed to be the crucial determinants of spermatogenesis (Navarro-Costa et al 2010;Lu et al 2014;Nailwal and Chauhan 2017). Because AZFc region contains long repeat DNA units, it is particularly prone to recombination events and, hence, to structural and deleterious variation in men (Navarro-Costa et al 2010;Lu et al 2014;Nailwal and Chauhan 2017), especially when exposed to genotoxic insult (Premi et al 2007(Premi et al , 2009Arruda et al 2008;Moghbeli-Nejad et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Much ongoing work in this field focuses on possible associations between spermatogenesis phenotypes and copy number variation in specific testis-expressed gene families (35,36,74,75,84).…”
Section: Searching For the Testis-determining Genementioning
confidence: 99%
“…Corroborating these observations further, copy number variations of DAZ and CDY1 genes were found to be associated with reduction in total motile sperm count in men harbouring AZFc subdeletions [37]. Recently, Lu et al also reported that loss of individual copies of genes within AZFc also lead to impaired spermatogenesis [38]. Thus it is possible that copy number variations of the DAZ and CDY1 genes may influence the sperm concentration and clinical manifestation of the men with AZFc subdeletions.…”
Section: Introductionmentioning
confidence: 81%